Provoking Curriculum as Inspirited Topographies: Frontispiece - St Georges, Darlene E (Journal of the Canadian Association for Curriculum Studies, 2016)
This arts-integrated work, "Root," reflects one of the sub-themes – Provoking Curriculum as Inspirited Topographies – of this special issue of JCACS. The theme and title of this special issue is "Canadian Curriculum Studies: A Métissage of Polyphonic Textualities."